1996
DOI: 10.1002/pssa.2211580106
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behaviour of CuCo Alloys

Abstract: The precipitation behaviour of Cu-1 at% Co and Cu-3 at% Co alloys under isothermal annealing was investigated. The present TEM and SEM work revealed that a coherent Co-rich precipitate with an octahedral shape surrounded by (110) planes was formed in the ageing process at 600 to 800 "C under zero magnetic field. Satellite precipitates were arranged adjacent to the parent large Co-rich precipitates in (100) directions.Es wurde die Eigenschaft von Cu-1 At% Co und Cu-3 At% Co Legierungen untersucht, wahrend des i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
5
9
0
Order By: Relevance
“…However, the cobalt precipitates resulting in precipitation hardening have been observed in fcc (1.0-2.8 at.%) Co-Cu alloys [65,66] and one can suggest their appearance in bcc Cu particles. Taking into account a possibility for cobalt clusters in bcc Cu, which was demonstrated in ''Additions in bulk bcc Fe and bcc Cu'' section, we now consider the preferable positions of cobalt dimer (25 % Co concentration in layer), trimer (37.5 % Co concentration in layer), as well as a Co monolayer (8 Co atoms or 100 % Co concentration in layer) in the Cu slab.…”
Section: Cobalt Segregationmentioning
confidence: 95%
“…However, the cobalt precipitates resulting in precipitation hardening have been observed in fcc (1.0-2.8 at.%) Co-Cu alloys [65,66] and one can suggest their appearance in bcc Cu particles. Taking into account a possibility for cobalt clusters in bcc Cu, which was demonstrated in ''Additions in bulk bcc Fe and bcc Cu'' section, we now consider the preferable positions of cobalt dimer (25 % Co concentration in layer), trimer (37.5 % Co concentration in layer), as well as a Co monolayer (8 Co atoms or 100 % Co concentration in layer) in the Cu slab.…”
Section: Cobalt Segregationmentioning
confidence: 95%
“…The previous work done by the present authors has revealed that coherent f.c.c. Co-rich precipitates have an octahedral shape, as based on images for different specimen orientations [13]. This work also pointed out the possibility that a special precipitation mechanism works in the aging process of the alloy, but the task of examining the full aging process was still left over.…”
Section: Introductionmentioning
confidence: 96%
“…Previous papers of the present group [6][7][8] have described microstructural studies of one type of granular magnetic material, namely Cu-Co alloys. These studies suggested that the precipitation of nano-scale ferromagnetic Co particles evolved under the influence of the magnetism of the particles.…”
Section: Introductionmentioning
confidence: 99%